Ethical Issues inthe Conduct of International Business: A Review of the Literature (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Worldwide concern for universally acceptable codes of ethical standards and guidelines in the conduct of international business was showcased. Related concepts, among them, the concepts of ethics corruption, bribery, theft and ethical dilemma, were also duly ventilated. Several examples of ethical breaches in the conduct of international business and how existing laws and regulations handled such cases were examined. Enforcement bodies created to combat and prosecute unethical business behaviours were found to be incapacitated by obvious inadequacies of the largely country-specific laws and regulations under which they operated.Perhaps actors in the international business arena must have expected too much from codes of ethical standards and guidelines developed by individual Multinational Corporations (MNCs) as these lacked consistency in their implementation and could hardly be effective within cross-cultural situations in which international businesses operate. The general feelingis that adherence to a set of universally acceptable ethical guidelines in the conduct of international business could be helpful in eliminating all forms of corruption